Shallow Suberitida (Porifera, Demospongiae) from Peru - Cóndor-Luján, B.; Arteaga, A.; Polo, C.; Arroyo, Y.; Willenz, P.; Hajdu, E. (Zootaxa, 2023)
This study describes 81 specimens belonging to Suberitida, collected during the projects Esponjas del Perú (ESPER), Esponjas da América do Sul (EsponjAS) and Semilla UCSUR 2019 (Demospongiae) along the coast of Peru, down to 30 m depth. Using morphological analyses, eight species were identified, one of which is new to science: Halichondria (H.) cristata, H. (H.) prostrata, Hymeniacidon perlevis, Johannesia reticulosa, Plicatellopsis expansa, Suberites aff. latus, Terpios cf. granulosus and Suberites inti sp. nov. Halichondria (H.) cristata, originally from Tierra del Fuego (SW Atlantic), was found widely distributed along the coast of Peru (06° S–14° S). The Magellanican H. (H.) prostrata and the formerly Chilean endemic P. expansa are extended up to Central Peru (12° S). Hymeniacidon perlevis, which presents a highly variable morphology (colour, shape, and spicule size), is firstly reported from the SE Pacific and its continuous occurrence in Peru (04° S–17° S) should be monitored given its supposed invasive potential. Johannesia reticulosa, previously known from Chile (20° S) and southern Peru (13° S), was found further north (11° S). Suberites latus and T. granulosus were originally recorded far-off from the Peruvian coast, in British Columbia and Hawaii, respectively. Thus, the occurrences of Suberites aff. latus and Terpios cf. granulosus are unexpected and should receive special attention in future molecular studies assessing their taxonomical status. Suberites inti sp. nov. characterised by its skeleton with ectosomal bouquets and multispicular choanosomal tracts, and two categories of straight tylostyles, is provisionally endemic to Paracas (13° S). With these results, the number of shallow Suberitida from Peru increases from 2 to 9. However, this number might rise as sampling in deeper environments could bring descriptions of new records.